The Kazakh-Singaporean joint ventures (International relations and international law Journal, 2016)
This article is devoted to analysis of the experience of functioning of the Kazakh-Singaporean joint ventures as one of the important forms of the foreign economic cooperation between the two countries. Authors analyzed and revealed the importance of gradually amplifying cooperation between Kazakh and Singaporean companies for increase of competitiveness of the domestic enterprises in the world market of finished goods, and also benefit of joint business in Kazakhstan for Singaporean companies is revealed.     Particular attention is paid to the most successful joint projects, such as joint ventures "Kaz-ST Bastau" and "Keppel Kazakhstan", the main directions and results of their activities throughout the years of operation in Kazakhstan. The article also identifies the problems and prospects of further functioning of joint Kazakh-Singaporean companies. In our opinion, the use of the Singaporean business experience and the work of joint ventures of the two countries are considered to be the efficient and promising area of cooperation between Kazakhstan and Singapore.
Keywords: Joint ventures; competitiveness; investments; high-tech spheres; innovations; oil infrastructure